2017
DOI: 10.1016/j.arthro.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Tear Progression of Symptomatic Full-Thickness and Partial-Thickness Rotator Cuff Tears as Measured by Repeated MRI

Abstract: calcaneus and talus. There was significantly more inversion in the subtalar joint than the tibiotalar joint with weight-bearing inversion. Conclusion: We found that with weight-bearing inversion of the ankle joint complex, there was significantly lower stiffness and torque following injury to both the ATFL and CFL, and sequentially greater inversion of the talus and calcaneus with progressive ligament injury. This corresponds to a shift in the COF in the tibiotalar joint and a reduction of peak pressure. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In previous studies, the majority of rotator cuff tears remain unchanged without an increase in tear size, despite no evidence of selfhealing in rotator cuff tears. 5,14 Considering the natural history of PTRCTs and the result of this study, a trial period of nonoperative care of PTRCTs seems reasonable, rather than prompt surgical repair. This will not only help with pain control but may also help avoid unnecessary surgical intervention for asymptomatic PTRCTs.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In previous studies, the majority of rotator cuff tears remain unchanged without an increase in tear size, despite no evidence of selfhealing in rotator cuff tears. 5,14 Considering the natural history of PTRCTs and the result of this study, a trial period of nonoperative care of PTRCTs seems reasonable, rather than prompt surgical repair. This will not only help with pain control but may also help avoid unnecessary surgical intervention for asymptomatic PTRCTs.…”
Section: Discussionmentioning
confidence: 90%
“…9 Furthermore, there is no clear clinical or biological evidence that nonoperative treatment will lead to actual healing of the tendon. 5,14 Practically, the problem regarding the nonoperative treatment of PTRCTs is the absence of clear indications for when surgical repair should be performed. There is no doubt that surgical intervention for PTRCT is necessary in the case of tear progression with accompanying discomfort/pain or functional disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Yang-Soo et al [34] found that 28 of 34 patients (82.4%) with symptomatic FTTs and 23 of 88 patients (26.1%) with symptomatic PTTs had tears that increased in size over a follow-up period of 6 months to 8 years. The clinical relevance of these observations is that FTTs treated conservatively should be monitored more carefully than PTTs for progression.…”
Section: Radiographic Changesmentioning
confidence: 99%
“…Some tears do increase in size, with greatest rate of increase in those with full-thickness tears; observed in 82% versus 26% of those with partial-thickness tears 8. But it is also apparent that many RC tears do not progress over time, and, importantly, these increases are not consistently associated with poorer outcomes of pain and function 8…”
mentioning
confidence: 99%